2011
DOI: 10.1016/j.ajpath.2010.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis Risk Genes of the Late Cornified Envelope-3 Group Are Distinctly Expressed Compared with Genes of Other LCE Groups

Abstract: Deletion of the late cornified envelope (LCE) genes LCE3B and LCE3C has recently been identified as a risk factor for psoriasis. Expression of 16 LCE genes of LCE groups 1, 2, 3, 5, and 6 was examined in vivo and in vitro. Quantitative PCR demonstrated that moderate to high LCE expression was largely confined to skin and a few oropharyngeal tissues. Genes of the LCE3 group demonstrated increased expression in lesional psoriatic epidermis and were induced after superficial injury of normal skin, whereas express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 28 publications
5
93
1
Order By: Relevance
“…These genes, in particular Lce, have been recently shown to be upregulated in response to skin barrier disruption (de Cid et al, 2009). Furthermore, Bergboer and collaborators showed that normal skin barrier function correlates with LCE groups 1, 2, 5 and 6, whereas expression of LCE3 genes is linked to barrier repair after injury or inflammation (Bergboer et al, 2011). These findings, in conjunction with the specific and prominent upregulation of expression of the Lce3 group in the Cyp26b1 -/-skin, suggest a mechanistic link between barrier disruption and inflammation in this mouse model that correlate with the systematic effects of increased RA levels.…”
Section: Discussionsupporting
confidence: 51%
“…These genes, in particular Lce, have been recently shown to be upregulated in response to skin barrier disruption (de Cid et al, 2009). Furthermore, Bergboer and collaborators showed that normal skin barrier function correlates with LCE groups 1, 2, 5 and 6, whereas expression of LCE3 genes is linked to barrier repair after injury or inflammation (Bergboer et al, 2011). These findings, in conjunction with the specific and prominent upregulation of expression of the Lce3 group in the Cyp26b1 -/-skin, suggest a mechanistic link between barrier disruption and inflammation in this mouse model that correlate with the systematic effects of increased RA levels.…”
Section: Discussionsupporting
confidence: 51%
“…They reported that the LCE1D gene could be detected in skin swabs for up to 21 storage days, and its expression decreased significantly in a time-dependent manner. In contrast to our findings, Bergboer et al (2011) reported that some LCE family genes were induced at the end of storage duration. They assumed that their methodology, storage media and irradiation could affect the expression levels of the LCE genes (Sampaio-Silva et al, 2013).…”
Section: Discussioncontrasting
confidence: 55%
“…However, our findings did not show any statistical significant difference. Similarly, Bergboer et al (2011) andSampaio-Silva et al (2013) found a high expression of LCE gene in skin samples when kept at room temperature (21°C ± 2). Another study by Lv et al (2014) found varied RNA expression and degradation behaviors and suggested that environmental factors could play a role in gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, this was demonstrated for LCE6A (6). Furthermore, we showed that LCE2 proteins are localized along the CE in human skin (3). In addition, we demonstrated that LCE3 group members are distinctly expressed compared with the expression levels of other LCE genes in normal and psoriasis skin and in normal skin before and after minor skin injury (3).…”
Section: Introductionmentioning
confidence: 79%